(untitled) (KYAMC Journal, 2020)
Background: Colistin-resistant Gram-negative bacteria is a rapidly emerging global threatgenerated a sense of public alarm. Objective: To combat this challenge a study was designedto evaluate the fast spreading infections by colistin-resistant pathogens in the tertiary care rural hospital of Bangladesh. Materials and Methods: To study isolation ofpathogenic gram-negative bacilli,clinical sample (n-640) of hospitalized patients of Khwaja Yunus Ali Medical College Hospital in Enayetpur, Bangladesh during the 1st quarter of the year 2019 were used. The bacterial isolates were screened for meropenem and colistin-resistance. Results: A total of 156 bacterial isolates were studied which included Escherichia coli (n-112), Klebsiella pneumoniae (n-14), Pseudomonas aeruginosa (n-27), and Salmonella typhi (n-3). Antibiotic sensitivity testing showed that 32/156(20%) and 119/156 (76%) isolates were resistant to meropenem and colistin, respectively. whereas 50/156 (32%) isolates were resistant to both antibiotics. Escherichia coli, K. pneumoniae, pseudomonas aeruginosa, and Salmonella typhi isolates respectivelywere 112/156 (72%), 14/156 (9%). 27/156 (17%), and 3/156 (2%). Conclusion: Colistin is typically used as salvage therapy, or last-line treatment, for MDR gramnegative infections.But there is worrisome therapeutic scenario in our study finding of colistin resistance is 76% in Gram-negative bacteria of the clinical isolates. The restricted and rational use of colistin drug is the need of hour. KYAMC Journal Vol. 11, No.-2, July 2020, Page 87-90